PERANAN PESANTREN DARULARAFAH DALAM PENGEMBANGAN MASYARAKAT DESA LAU BAKERI - Haidar Putra Daulay; Hasan Asari; Tirta Yogi Aulia (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This research aims to determine the extent to which the role of the Darularafah Raya Islamic boarding school towards the community in non-Muslim areas as well as as input for the same, similar or other institutions in playing a good role in education, religion and economy, this research is important because Darul Arafah Raya Islamic boarding school can develop and become the largest educational institution in a non-Muslim-majority area. This research uses a qualitative method with a historical approach. The informants are teachers, traders, community leaders and religious leaders. The research instrument is observation, interview and data documentation. Data analysis in this study includes data reduction, data presentation and conclusions. The data are validated by triangulation and diligent in observing. The results of this study are (1) The role of Darularafah Raya Islamic boarding school in village community education, namely as facilitators, educators, educational institutions, competitors (2) Roles in the religious field, namely facilitators, referrals and human resources (3) Roles in the economic field, namely as consumers, partners, providers of job vacancies. Novelty this research includes: Islamic religious education institutions are expected to play a role and implement and practice directly religious and general activities in a balanced manner in society so that the realization of wahdatul'ulum and moderation in religion and produce Muslim scholars who understand religion as well as technology experts.